Electric scooter-related orthopedic injuries: the experience of an Italian orthopedic center and literature review - Pietro Simone Randelli; Francesco Luceri; Valerio Monteleone (Trauma Surgery & Acute Care Open)
Background With the increasing prevalence of electric scooters, a concomitant increase in the number of specific injuries, emergency department (ED) admissions and hospital admissions have been reported.Objectives Analyze patient flow changes in the ED with a focus on e-scooter-related injuries through a case series and a comparison with the contemporary literature.Data sources A systematic literature review was performed on Medline/PubMed and Embase using terms related to the topic.Data collected from two-wheeled vehicle trauma patients at our Italian ED from May 1 to October 31, 2021, were analyzed for the case series.Study eligibility criteria Studies were included if they evaluated populations with an e-scooter-related injury referred to the ED with precise localization and nature of the injury reported.Participants and interventions Data collected from the literature studies and from our case series included overall ED patient numbers, patient demographics, injury mechanism, location of the injury, discharge diagnosis, and performance of surgery.Study appraisal and synthesis methods All studies were checked in order to establish the coherence with the purposes of this review. Data from the contemporary literature and from this case series were compared.Results During a 6-month period, 280 patients had e-scooter injuries, resulting in 292 traumas, including 123 fractures, primarily in the elbow. Surgical intervention was necessary for 28 patients. The review included nine papers, highlighting that injuries to the upper and lower extremities and head were frequent in e-scooter-related incidents. The upper extremities were the most common fracture location.Limitations The study is a retrospective, single-center study without a comparison group, focusing exclusively on orthopedic injuries.Conclusions or implications of key findings The prevalence of electric scooters, which offer an affordable and eco-friendly mode of transport, is steadily increasing. It is important to focus on injury risk mitigation through effective public health policies, thereby lowering costs to society.